Ramanujan Summation for Number of Diagonals in a Polygon - Kumar, A. Dinesh; Sivaraman, R. (Contemporary Mathematics, 2024)
Among several ideas existing in Summability Theory which deals with assigning finite values to infinite divergent series of real numbers, Ramanujan Summation is one among them. There is a well known compact formula for determining number of diagonals in a convex polygon with n sides. In this paper, we will prove a new result pertaining to determining Ramanujan Summation for the divergent series whose terms are positive integral powers of number of diagonals in an n sided convex polygon.